Risk Perception for Developing Erectile Dysfunction among Malaysian Men with Type 2 Diabetes Mellitus - Mohamad, Anuar; Tohid, Hizlinda; Ahmad, Saharuddin; Tong, Seng Fah; Ahmad, Mahadir (UI Scholars Hub, 2021)
Risk perception for developing erectile dysfunction (ED) is an appreciation of the susceptibility to having ED and its severity. This study examined this risk perception and its associated factors among 180 men with type 2 diabetes mellitus (T2DM), who claimed not to have ED. This cross sectional study was conducted at a public health clinic using a validated self-administered questionnaire, which assessed participant characteristics, perceived susceptibility to developing ED, perceived severity of ED, and knowledge on risk factors for ED. About 71.1% had an inaccurate perception of susceptibility to developing ED and their perception on its severity was moderate (median (IQR) score: 10.0 (6.0); range score: 3–15; midpoint: 9). In multiple linear regression, having ED symptoms (p-value < 0.001) and secondary (p-value = 0.045) or tertiary education (p-value: 0.022) significantly contributed to a higher perception of susceptibility. A higher perception of severity was significantly found in Malays (p-value < 0.001), the employed (p-value = 0.026), and those with better knowledge on risk factors for ED (p-value < 0.001). Risk perception for developing ED among men with T2DM appears poor and it was significantly influenced by sociocultural factors, educational attainment, ED symptoms, and knowledge on risk factors for ED. Thus, to improve their risk perception, they should be provided appropriate counseling and education.